Amine Oxidases of Marine Phytoplankton - Palenik, Brian (1991)
Some phytoplankton utilized a novel mechanism for obtaining nitrogen from primary amines. They oxidized the primary amines to produce extracellular hydrogen peroxide and aldehydes and used the third reaction product, ammonium, as a nitrogen source. The specificity, regulation, inhibition by bromoethylamine, and potential dependence on copper of this process are described.